Impact of Life Events upon Onset of Depression Disorder In AL-Diwanyia Governorate : A Case-Control Study - jabor, Haider; AL-Juboor, ali (Iraqi National Journal of Nursing Specialties, 2012)
Objective: The aim of this study is to find out the impact of life events upon onset of depression, to describe theprevalence of life events among depressed patients.Methodology: Retrospective a case-control study conducted in AL-Diwanyia Teaching Hospital, PsychiatricDepartment on A non-probability (purposive sample) of (60) depressed patients and (60) of healthy person were matchedwith them from general population. The data were collected through the use of semi-structured interview byquestionnaire, which consists of two parts (1) divide, section A. cover letter and B. Sociodemographic data which consistsof 9-items, (2) Life events questionnaire consists of 51-items distributed to six dimensions include, family and socialdimension, financial dimension, work and school dimension, legal and criminal dimension, health dimension and changeof residency dimension.Results: The findings of the present study indicate that the depressed patients have more exposed to life events thancontrol group before one year of onset of depression, family and social dimension, financial dimension, legal and criminaldimension more effect on depression onset.Recommendations: The study recommends that increase the individual, family and community awareness aboutstress management to decrease the impact of life events upon their health.